2019
DOI: 10.1111/jcpe.13177
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome in maintained periodontitis and its shift over a single maintenance interval of 3 months

Abstract: Aim To assess the subgingival microbial shift of maintained periodontitis treated by ultrasonic scaling (US) or air polishing (AP) during a 3‐month maintenance interval. Materials and methods We conducted a 12‐week randomized split‐mouth controlled trial with US and AP in 17 maintained subjects (bleeding on probing [BOP%] ≤25%, probing depth [PD] ≤5 mm). They were monitored at baseline, week 2, week 8 and week 12. The V3‐V4 region of the 16S rDNA from 136 subgingival plaque samples was sequenced and analysed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(51 citation statements)
references
References 44 publications
3
36
0
Order By: Relevance
“…Well-maintained subjects with a history of periodontitis were from a longitudinal trial 9 4. BOP (%) ≤ 25%; 5.…”
Section: Participantsmentioning
confidence: 99%
See 3 more Smart Citations
“…Well-maintained subjects with a history of periodontitis were from a longitudinal trial 9 4. BOP (%) ≤ 25%; 5.…”
Section: Participantsmentioning
confidence: 99%
“…8 Supportive periodontal treatment could effectively remove dental plaque and keep a relatively balanced microbial community. 9 However, many epidemiological studies demonstrated that maintained patients still had a higher risk of recurrence as compared with periodontally healthy individuals. 10,11 It is generally accepted that the challenge of bacteria and host susceptibility are the two main factors accounting for the progress of periodontitis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 21 ] Microbial shifts following treatment have also been studied, but with less consistent findings. [ 8,22–24 ] Divergences in the microbial profiles according to the treatment outcome (successful or not) are also not well characterized. [ 25 ]…”
Section: Introductionmentioning
confidence: 99%